LEARNING MIND MAP FOR CREATIVE THINKING - Anggita Maharani (Journal Of Educational Experts (JEE), 2018)
Abstract Learning Mathematics should be given to all children as a basis for logical thinking, analytical, systematic, critical, and creative, as well as the ability to cooperate. Creativity is essentially a person's ability to create something new in the form of ideas and real work in the form of new works as well as a combination of things that already exist. Creativity in mathematics is known as creative thinking. Learning Mind Map is a learning technique that utilizes the entire record of the brain by using visual images and other graphical infrastructure to form an impression of the more interesting so that students can describe the concept of a material with their own creativity in terms of both language and symbols. Through the Mind Map, we can see the whole description of the material we are studying, activates the whole brain works to develop and plan the direction of mind maps, solve a problem by making a creative breakthrough, it is easier to remember the information in a clear and easy to understand, and get something fun and creative Keywords:        Mathematical Creativity, Learning Mind Map